2016
DOI: 10.1186/s12966-016-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Does duration of physical activity bouts matter for adiposity and metabolic syndrome? A cross-sectional study of older British men

Abstract: BackgroundOlder adults have low physical activity(PA) and high sedentary behaviour(SB) levels. We investigate how total volume and specific patterns of moderate to vigorous PA(MVPA), light PA(LPA) and SB are related to adiposity and metabolic syndrome (MS). Then, with reference to physical activity guidelines which encourage MVPA in bouts > =10 min and avoiding “long” sedentary bouts, we investigate whether accumulating PA and SB in bouts of different defined durations are differently associated with these out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
124
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 33 publications
12
124
1
6
Order By: Relevance
“…We found associations with successful ageing to be similar for MVPA bouts lasting less than 10 minutes and 10 minutes or more. Few previous studies reported similar association with time spent in short and long bouts of MVPA with cardio-metabolic outcomes202122 and multimorbidity23. Indeed, bouts of MVPA of at least 10 minutes are recommended for cardiorespiratory fitness648, although appropriate experimental studies to assess associations between duration spent in different lengths of MVPA bouts and health outcomes are lacking48.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found associations with successful ageing to be similar for MVPA bouts lasting less than 10 minutes and 10 minutes or more. Few previous studies reported similar association with time spent in short and long bouts of MVPA with cardio-metabolic outcomes202122 and multimorbidity23. Indeed, bouts of MVPA of at least 10 minutes are recommended for cardiorespiratory fitness648, although appropriate experimental studies to assess associations between duration spent in different lengths of MVPA bouts and health outcomes are lacking48.…”
Section: Discussionmentioning
confidence: 99%
“…To remove signals related to random wrist movement, we only retained activities lasting at least 1 minute for which 80% of the activity satisfied the 100 m g threshold criteria. In order to test the importance of length of a bout of physical activity, we identified bouts lasting 1 to 9 minutes 59 seconds and those lasting 10 minutes or more, hereafter labeled “short” and “long” bouts2021 (further details in Supplementary Methods). Time spent in MVPA bouts lasting 1 minute or more was calculated as the sum of short and long bouts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it could be argued that examining accumulated time in MVPA regardless of bout lengths is more appropriate given the old age group in the current study, as maintaining longer episodes of MVPA may be more challenging in this age group compared to younger counterparts. Furthermore, a study based on a sample of older men recently showed that strength in associations between markers for metabolic risk and daily time in MVPA did not differ depending on whether time in MVPA was derived in consecutive time bouts or just accumulated over the day [33]. …”
Section: Discussionmentioning
confidence: 99%
“…However, to more precisely determine associations between PA and disease characteristics across the spectrum of PA intensity, accelerometer‐based measures are preferable. Compared with studies using self‐reported PA, fewer studies have been published in which accelerometer‐measured PA has been related to CVD risk factors in adults . Previous studies often have included relatively small sample sizes, and few have reported results in older postmenopausal women .…”
Section: Introductionmentioning
confidence: 99%